Discrepancy between tissue factor activity and tissue factor expression in endotoxin-induced monocytes is associated with apoptosis and necrosis - Henriksson, Carola E; Klingenberg, Olav; Ovstebø, Reidun; Joø, Gun-Britt; Westvik, Ase-Brit; Kierulf, Peter (Thrombosis and haemostasis, 2005)
Tissue factor (TF), the main initiator of blood coagulation, contributes to the manifestation of disseminated intravascular coagulation following septic shock in meningococcal infection. Since a direct relationship between disease severity and lipopolysaccharide (LPS) concentration in the circulation has been shown, we hypothesized that the procoagulant and cytotoxic effects of endotoxin also in vitro were related to its concentration. In vitro studies, however, have frequently used much higher LPS concentrations than those observed in clinical samples. Using elutriation-purified human monocytes, we observed that LPS up to 1000 ng/ml exerted a concentration-dependent increase in TF activity (tenase activity, fibrin formation in plasma). Although there was a dose-dependent increase in TF activity, there was not a concomitant increase in TF expression at LPS concentrations above 1 ng/ml (flow cytometry, Western blotting, TF mRNA). Flow cytometry revealed that this discrepancy between TF activity and TF expression at endotoxin concentrations above 1 ng/ml, coincided with an LPS dose-dependent increase in cell surface phosphatidylserine (PS), considered to promote coagulation. The increased PS expression was associated with an increased number of 7-AAD-positive cells indicating cell death. We conclude that enhancement of monocyte procoagulant activity in vitro by high concentrations of LPS may result from increased PS exposure due to apoptosis and necrosis. Therefore, the LPS concentrations used to examine monocyte procoagulant activity in vitro, should be carefully chosen.